Persepsi Picture Health Warning Dengan Perilaku Merokok Pada Masyarakat Di Desa Siti Ambia Aceh Singkil - M.Ahlun Fajar Cibro; Mulia Siregar (Universitas Medan Area, 2022)
This article aims to determine the relationship between the perception of Picture Health Warning and men who smoke in the village of Siti Ambia. This research method uses quantitative methods. The population of this study was 1,918 people and a sample of 237 people in the village of Siti Ambia, the researchers used a non-probability sampling technique, namely accidental sampling. The results showed that there was a significant negative relationship between the perception of health warning images and smoking behavior seen from the coefficient value (Rxy) = - 0, 144 with p = 0.027 in the community in the village of Siti Ambia, meaning the hypothesis that there is a negative relationship and significant perception of health warning images with smoking behavior is accepted, as well as the value (R2) which has a value of 0.021 this is equivalent to 2.1% meaning that the perception of health warning images contributes 2.1% (low) to the community in the village of Siti Ambia, it can be said that the contribution raised by the perception of picture health warning in reducing smoking in the village of siti ambia.